The Influence of Perceived Usefulness and Perceived Ease of Use on Intention To Use in Using QRIS According to an Islamic Business Perspective (Study of QRIS Users at Geprek King Sukarame Restaurant in Bandar Lampung) - Adil Wahid, Muhammad Fariz; Fuadi, Fatih; Ermawati, Liya (ProBisnis : Jurnal Manajemen, 2024)
The use of QRIS is the desire to use QRIS as a payment method, this is influenced by how useful and easy the technology is to use in transactions. The higher the usefulness and ease, the greater the intention to use QRIS. This study aims to determine how much influence Perceived Usefulness, and Perceived Ease of Use have on Intention To Use on the use of QRIS in an Islamic business perspective. The study used a quantitative method, the population was QRIS users at the Geprek King Restaurant. Sampling using purposive sampling technique, the number of samples was 100 respondents using the Lemeshow formula. The method using multiple linear regression analysis was processed using IBM SPSS version 23. The results showed that Perceived Usefulness had a significant effect on Intention to Use QRIS, meaning that the higher the perception of the usefulness of technology, the greater the user's intention to continue using it. Perceived Ease of Use had a significant effect on Intention to Use, indicating that the ease of use of technology encouraged more frequent use of it. Simultaneously, Perceived Usefulness and Perceived Ease of Use have a significant effect on Intention to Use QRIS, proving that the higher the usefulness and ease, the greater the user's intention to use it continuously. From an Islamic business perspective, high Perceived Usefulness and Perceived Ease of Use of technology, such as QRIS, increases the user's intention to use it continuously, as long as the technology is in line with sharia principles.